Pengaruh Strategi Inovasi dan Orientasi Kewirausahaan Terhadap Keunggulan Bersaing dan Kinerja Pemasaran (Studi UMKM Kabupaten Pangkep) - Ifadhila Ifadhila; Yunarti Yunarti; Muh Amrih (Jurnal Impresi Indonesia, 2025)
This research is motivated by the importance of innovation and entrepreneurial orientation in improving the competitiveness and marketing performance of MSMEs in the era of global competition. The purpose of this study is to analyze the influence of innovation strategy and entrepreneurial orientation on the competitive advantage and marketing performance of MSMEs in Pangkep Regency. This study uses a quantitative approach with an explanatory method to explain the causal relationship between variables. Data were collected through a Likert-scale questionnaire from 92 MSME owner respondents selected using a non-probability sampling technique, namely accidental/convenience sampling. Data analysis was carried out using Structural Equation Modeling Partial Least Squares (SEM-PLS) in SmartPLS. The results showed that innovation strategy significantly influenced competitive advantage (t = 2.009; p = 0.045), while entrepreneurial orientation significantly influenced marketing performance (t = 2.793; p = 0.005), and competitive advantage significantly influenced marketing performance (t = 5.752; p = 0.000). Furthermore, competitive advantage served as a mediating variable, strengthening the influence of innovation strategy (t = 2.693; p = 0.007) and entrepreneurial orientation on marketing performance (t = 2.352; p = 0.019). This finding confirms that competitive advantage is a key factor in improving the marketing performance of MSMEs in Pangkep Regency.